Beyond Glycemic Control in Diabetes Mellitus: Effects of Incretin-Based Therapies on Bone Metabolism - CECCARELLI, ELENA; GUARINO, ELISA; MERLOTTI, DANIELA; PATTI, AURORA; GENNARI, LUIGI; NUTI, RANUCCIO; DOTTA, FRANCESCO (Frontiers in Endocrinology, 2013)
Diabetes mellitus (DM) and osteoporosis (OP) are common disorders with a significant health burden, and an increase in fracture risk has been described both in type 1 (T1DM) and in type 2 (T2DM) diabetes. The pathogenic mechanisms of impaired skeletal strength in diabetes remain to be clarified in details and they are only in part reflected by a variation in bone mineral density (BMD). In T2DM, the occurrence of low bone turnover together with a decreased osteoblast activity and compromised bone quality has been shown. Of note, some antidiabetic drugs (e.g. tiazolidinediones, insulin) may deeply affect bone metabolism. In addition, the recently introduced class of incretin-based drugs (i.e. GLP-1 receptor agonists and DPP-4 inhibitors) is expected to exert potentially beneficial effects on bone health, possibly due to a bone anabolic activity of GLP-1, that can be either direct or indirect through the involvement of thyroid C cells. Here we will review the established as well as the putative effects of incretin hormones and of incretin-based drugs on bone metabolism, both in preclinical models and in man, taking into account that such therapeutic strategy may be effective not only to achieve a good glycemic control, but also to improve bone health in diabetic patients.